THE CODE OF CONSUMER PROTECTION AND CONSUMER VULNERABILITY OF THE RELIGIOUS CULTURAL INDUSTRY FACING THE PRINCIPLE OF RELIGIOUS FREEDOM (Revista Direito em Debate, 2019)
The study analyzes the controversy of the religious cultural industry and the possible ways of assuring the right of the loyal consumer when there is any abuse of the religious authority considered as provider of goods and services, contrary to the principle of religious freedom. It concludes that the Consumer Protection Code (1990) is the main legislative source through which the loyal consumer may appeal to resolve conflicts related to the failure to provide promised religious services, the costly offering being an offense to religious freedom. The theoretical-bibliographic research uses the hypothetical-deductive methodological procedure to delimit the theoretical problem and the technical procedure, interpretative, comparative, historical and thematic analysis, allowing discussion based on the point of view of scientific criticism.
Keywords: CONSUMER LAW; RELIGIOUS FREEDOM; Religious Consumption Relationship; Loyal consumer vulnerability